Kewenangan Jaksa Agung Dalam Mengesampingkan Perkara Demi Kepentingan Umum - Kiki Astuti Wulandary Sutin (Kalabbirang Law Journal, 2021)
Penelitian ini bertujuan; Pertama mengetahui penerapan pengesampingan perkara dalam memenuhi adanya kepentingan umum, dan Kedua mengkaji dampak yang ditimbulkan dengan tidak adanya instrumen hukum untuk melakukan perlawanan terhadap keputusan pengesampingkan perkara demi kepentingan umum. Penelitian ini merupakan tipe penelitian normative dengan menggunakan pendekatan undang-undang, pendekatan kasus, pendekatan perbandingan, dan pendekatan konseptual. Hasil penelitian ini menunjukkan: Pertama Pengesampingan perkara terhadap perkara Abraham Samad dan Bambang Widjojanto dengan pertimbangan Jaksa Agung belum menunjukkan terganggunya kepentingan umum secara nyata; Kedua Tidak ditemukan adanya mekanisme untuk melakukan perlawanan atau upaya hukum terhadap keputusan pengesampingan perkara oleh Jaksa Agung sebagai bentuk kebebasan kebijaksanaan (beleidvrijheid) menimbulkan dampak yakni, keputusan pengesampingan perkara oleh Jaksa Agung bersifat final dan mengikat (final and binding),tidak mengakomodir hak-hak korban kejahatan sesuai prinsip perlakuan yang sama di hadapan hukum, dan kewenangan tersebut rawan terhadap penyalahgunaan kekuasaan. The study aims to : (1) describe the public interest that becomes the basis of a general attorney in dismissing a case; (2) explain the implementation of dismissing a case to fulfill the public interest reason; and (3) analyze the impact caused by the absence of law instrumen againts the decision of dismissing a case for public interest. This research was a normative study usinglegal approach, case approach, comparative approach, and conceptual approach. It was conducted atthe Provincial Attorney General’s Office of South Sulawesi. The results show that:(1) In the dismissing of a case, public interest indicates the existence of state’s interest and community interest. This is in line with the explanation of article 35 letter c of the Act Number16 of 2004 that have to. The scope is broadand there is no standard in defining the public interest. Therefore, it needs to be considered within the context of state’s constitutional principleaccording to the Preamble of 1945 Constitution. (2) The dismissing of the case of Abraham Samad and Bambang Widjojanto with the consideration of Attorney General have not indicatedthe disturbance of public interest. (3) There is no anymechanism to appealagaints the general attorney’s decision to dismiss a case as a form of wisdom (beleidvrijheid), which caused some impacts namely the decision of general attorney to dismiss a case is final and binding, does not accommodate the rights of victims according to the principle of equality before the law, and vulnerable to abuse of power.